From Seeing to Being Subliminal Social Comparisons Affect Implicit and Explicit Self-Evaluations. (article). - Stapel, Diederik A.
The authors hypothesized that social comparisons can have automatic influences on-self-perceptions.This was tested by determining whether subliminal exposure to comparison information influences implicit and explicit self-evaluation. Study 1 showed that subliminal exposure to social comparison information increased the accessibility of the self. Study 2 revealed that subliminal exposure to social comparison information resulted in a contrast effect on explicit self-evaluation. Study 3 showed that subliminal exposure to social comparison information affects self-evaluations more easily than it affects mood or evaluations of other people. Studies 4 and 5 replicated these self-evaluation effects and extended them to implicit measures. Study 6 showed that automatic comparisons are responsive to a person's perceptual needs, such that they only occur when people are uncertain about themeselves. Implications for theories of social cognition, judgement and comparison are discussed.-- (from the author)